ANALISIS ZAT PEWARNA RHODAMIN B PADA KERUPUK YANG BEREDAR DI KOTA MANADO - Dawile, Sherly; Fatimawali, Fatimawali; Wehantouw, Frenly (PHARMACON, 2013)
ABSTRACT Rhodamine B dye in the form of a crystalline powder green or reddish purple, odorless, and dissolves easily in bright red solution berfluoresan as textile dyes. Rhodamine B is still no food products were found to contain rhodamine B dye such as crackers, sauces, ice and other pastries. The purpose of this study is to investigate and determine the levels of rhodamine B on crackers circulating in the city of Manado. Sampling sites crackers are 4 market in the city of Manado is Tuminting Market, Market Paal 2, Market Market Bersehati 45 and 45. Samples with ammonia to soak interesting rhodamine B dye using wool yarn, followed by identification using thin layer chromatography (TLC) and then in detection with UV light 254 nm and 366 nm. The reading levels of rhodamine B using UV-Vis spectrophotometry. The results showed that of the ten samples tested with three times obtained one positive sample containing rhodamine B with an average concentration value of rhodamine B in a sample of 45 markets in the sword of 0.28 mg/ml. Based on these results, some crackers circulating in Manado City Market unsafe consumed. Keywords: Rhodamine B, Crackers, spectrophotometry and Thin Layer Chromatography